Rock mass mechanical behavior assessment at the Porce III underground hydropower central, Colombia-South America (2008)
Abstract: Experimental and analytic methods, as also the observational method, have been used to accomplish the assessment of the good quality gneissic rock mass behavior at the underground central of the Porce III hydroelectric project, in Colombia, South America. This study encompassed complementary specialized testing in the rock material and it required that the field work be extended, in order to obtain the rock mass description. The following outstanding results are emphasized: the finding of stress-strain properties for a linear elastic transversal isotropic rock material and the peak/residual Drucker-Prager failure envelopes for different foliation joints inclinations; as well as the description, classification and possible origin of the actual rock mass discontinuities. The in-situ observational process was followed, up to a relevant excavations stage of the central, and it consisted of the exposed surfaces; and in processing the data readings of the multiple position extensometers and of the superficial convergence displacement points. The data obtained in this work were useful for the calibration of the wedge and of the two dimensional stress-strain models, which were subsequently used for the assessment of the rock mass mechanical behavior at the final excavation stages, and for the verification of the stability of the observational method is an adequate procedure to monitor large opening excavations during construction, as it provides more valid facts to understand the rock mass mechanical behavior.